Validation of app-based hearing assessment (H3 hearing test) through smart phone: preliminary trends. (2nd October 2022) - Katyayan, Adri; Katyayan, Angira; Rajput, Arti; Chandra, Manish; Verma, Veerendra; Mishra, Anupam
Abstract: Objective: To promote tele-audiology, the smartphone online applications (APP) for assessment of hearing function need to be validated. We present our preliminary report of one such APP that we adapted during the active COVID phase of 2021. Methodology: A total of 44 patients underwent both pure tone audiometry (PTA) and APP-based hearing assessment. The air conduction thresholds at 500 Hz, 1000 Hz, 2000 Hz, 3000 Hz, 4000 Hz, 6000 Hz and 8000 Hz were noted. Results: A significant correlation was seen between the thresholds and paired differences. However, air-conduction (AC) thresholds of either PTA or APP were shown to overshoot each other and right side values were more consistent. Conclusions: While suggestions have been made to overcome these inconsistencies, the APP-based hearing assessment is likely to improve tele-audiology as relevant modifications by the manufacturer are incorporated to improve its efficacy.